2009
DOI: 10.2147/copd.s4854
|View full text |Cite
|
Sign up to set email alerts
|

Change in inflammation in out-patient COPD patients from stable phase to a subsequent exacerbation

Abstract: BackgroundInflammation increases during exacerbations of COPD, but only a few studies systematically assessed these changes. Better identification of these changes will increase our knowledge and potentially guide therapy, for instance by helping with quicker distinction of bacterially induced exacerbations from other causes.AimTo identify which inflammatory parameters increase during COPD exacerbations compared to stable disease, and to compare bacterial and non-bacterial exacerbations.MethodsIn 45 COPD patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
78
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 42 publications
7
78
0
3
Order By: Relevance
“…This present inflammatory response, caused mostly by bacterial infections of lower airways, is higher than in the stable disease. 13 Potential mechanisms for this increased systemic inflammation in COPD exacerbation include: (1) spillover of inflammatory mediators from the pulmonary compartment; (2) an inflammatory reaction to tissue hypoxia; and (3) a reaction induced by the pro-inflammatory bacterial product lipopolysaccharide. 14 Several studies showed that inflammatory markers, such as circulating neutrophil numbers, C-reactive protein, fibrinogen, interleukin-6, interleukin-8, and soluble intercellular adhesion molecule 1, are increased during COPD exacerbation.…”
Section: Discussionmentioning
confidence: 99%
“…This present inflammatory response, caused mostly by bacterial infections of lower airways, is higher than in the stable disease. 13 Potential mechanisms for this increased systemic inflammation in COPD exacerbation include: (1) spillover of inflammatory mediators from the pulmonary compartment; (2) an inflammatory reaction to tissue hypoxia; and (3) a reaction induced by the pro-inflammatory bacterial product lipopolysaccharide. 14 Several studies showed that inflammatory markers, such as circulating neutrophil numbers, C-reactive protein, fibrinogen, interleukin-6, interleukin-8, and soluble intercellular adhesion molecule 1, are increased during COPD exacerbation.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous investigators have used various techniques to characterize the inflammatory response, including sputum analyses, bronchoalveolar lavage (BAL), bronchial biopsy, and blood markers. Several reports have confirmed an augmented inflammatory response in sputum, particularly during an AECOPD (14)(15)(16)(17)(18)(19); neutrophilic and eosinophilic inflammation have been described. In addition, a multitude of inflammatory mediators have been implicated (14-17, 19, 20).…”
Section: Copd Is An Inflammatory Disorder With Both Local and Systemimentioning
confidence: 86%
“…During acute exacerbation, many inflammatory biomarkers and cells increase in blood and sputum [5]. Previous studies revealed that systemic biomarker levels increased and this was related to prognosis and mortality [13,15]. C-RP is the most sensitive acute inflammation indicator [5].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to increase in difficulty of breathing, it must be accompanied by at least two of the things below for 24 hours or longer increase in coughing frequency or severity, increase in purulence or amount of sputum and wheeze [13]. Hospitalization criteria were made according to previous study [14].…”
Section: Defining Copd-aementioning
confidence: 99%